2003
DOI: 10.1074/jbc.m302045200
|View full text |Cite
|
Sign up to set email alerts
|

Previtamin D3 with a trans-Fused Decalin CD-ring Has Pronounced Genomic Activity

Abstract: 1,25(OH) 2 D 3 has a central rigid CD-bicyclic ring portion to which two flexible entities, the side chain and the seco-B,Aring, are connected. The characteristic seco structure of vitamin D 3 originates from the photolytic cleavage of the provitamin 7-dehydrocholesterol. The resulting previtamin triene (previtamin D 3 ) then reversibly thermo-isomerizes to the vitamin form in its less stable 6-s-cis conformation. Rapid rotation about the C6-C7 single bond eventually yields vitamin D 3 in its more stable exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This previtamin analog represents the first previtamin with potent vitamin-D-like activity which acts through the genomic signal transduction pathway as it could bind to VDR and was equipotent to 1,25(OH) 2 D 3 in inducing interaction with VDREs and the coactivator TIF-2. Mutational analysis and in silico docking suggested that this 19-nor-trans-decalin-1,25(OH) 2 -previtamin D 3 made similar contacts with the ligand-binding pocket as 1,25(OH) 2 D 3 [26].…”
Section: Decalin Analogsmentioning
confidence: 95%
See 1 more Smart Citation
“…This previtamin analog represents the first previtamin with potent vitamin-D-like activity which acts through the genomic signal transduction pathway as it could bind to VDR and was equipotent to 1,25(OH) 2 D 3 in inducing interaction with VDREs and the coactivator TIF-2. Mutational analysis and in silico docking suggested that this 19-nor-trans-decalin-1,25(OH) 2 -previtamin D 3 made similar contacts with the ligand-binding pocket as 1,25(OH) 2 D 3 [26].…”
Section: Decalin Analogsmentioning
confidence: 95%
“…Interestingly, the previtamin configuration of the biologically potent 19-nor-trans-decalin-1,25(OH) 2 D 3 (19-nor-trans-decalin-1,25(OH) 2 -previtamin D 3 , GAO182) was able to inhibit cell proliferation and induce cell differentiation to the same extent as 1,25(OH) 2 D 3 [26]. This previtamin analog represents the first previtamin with potent vitamin-D-like activity which acts through the genomic signal transduction pathway as it could bind to VDR and was equipotent to 1,25(OH) 2 D 3 in inducing interaction with VDREs and the coactivator TIF-2.…”
Section: Decalin Analogsmentioning
confidence: 98%
“…The mechanistic basis for the discrepancy between receptor binding and biological activity may be attributed to changes in VDR conformation and a modified interaction of liganded VDR with co-activator molecules, which alters the structural and functional properties of the entire DNA-binding complex. [7] Interestingly, introduction of a side chain at position C18 led to a decrease in calcemic activity. Indeed, in comparison with compound 1 a, at least 600-fold higher doses of the seven-or eight-membered C18 side chain analogues could be administered on a daily basis in NMRI vitamin D-replete mice ( Table 1).…”
Section: Biological Evaluationmentioning
confidence: 99%
“…However, other mechanisms such as increased metabolic degradation, tissue-specific differences in the binding affinities of compound 1 a and its analogues for the VDR, and different signaling pathways have been suggested to contribute. [7,8] The low calcemic activity of compound 2 a together with its potent antiproliferative and prodifferentiating activity make this compound appealing for therapeutic application.…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation